2009
DOI: 10.1007/s00464-008-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-controlled versus volume-controlled ventilation during one-lung ventilation in the prone position for robot-assisted esophagectomy

Abstract: Background The prone position during robotic esophageal mobilization for minimally invasive esophagectomy (MIE) provides several advantages with regards to operative times, surgeon ergonomics, and surgical view; however, this technique requires one-lung ventilation (OLV). There are no guidelines about ventilatory modes during OLV in the prone position. We investigated the effects of volume-controlled (VCV) and pressurecontrolled ventilation (PCV) on oxygenation and intrapulmonary shunt during OLV in the prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…However, owing to recent developments in laparoscopic techniques, intrathoracic procedures can be performed using thoracoscopy. Prone positioning of the patient during an intrathoracic procedure facilitates optimal exposure of the esophagus by means of the anatomical orientation in the prone position, thereby affording an excellent surgical view [3]. Furthermore, good exposure of the esophagus is achieved by inducing a transitory pneumothorax using carbon dioxide (CO 2 ) [4].…”
mentioning
confidence: 99%
“…However, owing to recent developments in laparoscopic techniques, intrathoracic procedures can be performed using thoracoscopy. Prone positioning of the patient during an intrathoracic procedure facilitates optimal exposure of the esophagus by means of the anatomical orientation in the prone position, thereby affording an excellent surgical view [3]. Furthermore, good exposure of the esophagus is achieved by inducing a transitory pneumothorax using carbon dioxide (CO 2 ) [4].…”
mentioning
confidence: 99%
“…Compared with the standard da Vinci, da Vinci S is improved not only in the risk of arms and the high-definition vision system, but also in the length of the instruments, variation in available instruments, range of arm motion, and number of collisions between the arms. Most of the recent reports of robotic esophagectomy describe the use of da Vinci S (1,10,11), and these procedures cannot be performed using a 3-arm standard da Vinci system because of limitations arising from the number of arms and length of the instruments. Furthermore, the instruments available for use with a da Vinci Surgical System are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, initial studies comparing PCV and volume-control ventilation (VCV) during OLV found improved oxygenation and shunt fraction with PCV 15 , as well as the risk reduction for post-thoracotomy acute lung injury, but subsequent investigations failed to highlight benefit of PCV during OLV. 8,[16][17][18] Traditionally, the lateral decubitus position has been found to improve oxygenation during OLV due to gravity redistribution of pulmonary blood flow with diverting roughly 10% of CO to the dependent lung. 19 On the other hand, Yatabe et al found better PaO 2 /FiO 2 ratios in patients undergoing oesophagectomy in prone position.…”
Section: The Impact Of Ventilation Strategy and Patient Positioning Omentioning
confidence: 99%